Evolutionary dynamic optimization techniques for marine contamination problem - TOPCUOĞLU, HALUK RAHMİ; ALTIN, LOKMAN (Association for Computing Machinery, Inc, 2015)
Marine pollution is the release of by-products that cause harm to natural marine ecosystems and one of the most important sources is the discharge of oil, ballast water from vessels. If the relevant technology is not available, alternative way to monitor environmental pollution is to use unmanned air vehicles (UAVs). Since the navigating vessels move in different directions and speeds, the determination of the tour that should be traveled by a UAV resembles to the dynamic traveling salesman problem (DTSP) in many aspects. This paper addresses a new type of DTSP, where targets can move in different directions with different speeds. The locations of all vessels can change due to changes in velocity that alters the length of all edges. Consequently, this problem has a higher complexity in comparison to classical DTSP presented in the literature. An empirical study is conducted to evaluate performance of selected evolutionary dynamic optimization techniques on solving the problem. © Copyright 2015 ACM.
Keywords: Dynamic traveling salesman problem; Evolutionary dynamic optimization